Study the Usage of 5G Technology in the ECRL Project - Ab Razak, Nurdalila Ayuni; Omar, Roshartini; Goh, Kai Chen; Mohamed, Sulzakimin (Research in Management of Technology and Business, 2024)
Using 5G technology in the construction industry can revolutionize and enhance various aspects of construction projects. With its high-speed, low-latency connectivity, and capacity to handle massive data transfers, 5G offers significant advantages for improved productivity, safety, collaboration, and operational efficiency in construction. These systems can be controlled and coordinated remotely, increasing efficiency, reducing labor requirements, and improving safety on construction sites. The successful implementation of 5G technology in the construction industry requires collaboration between construction companies, telecommunication providers, and technology vendors. Adequate infrastructure and coverage must be established to ensure reliable 5G connectivity on construction sites and robust security measures to protect sensitive data and privacy. However, 5G lack awareness and is low level in the necessity of 5G technology in the construction industry and this shows the problem where the use of 5G is not widely used in the construction industry. The research objective explains the level of awareness of 5G technology in construction, the level of necessity of 5G technology in construction, and the strategies that can be implemented in the usage of 5G technology in the construction industry. Therefore, this research uses a quantitative method involving a total of 32 respondents out of 436 respondents. In data analysis, this study uses Statistical Package for the Social Science (SPSS) version 27.0. The results of the research show that the first objective is the level of awareness of 5G technology in the construction industry was high. Furthermore, the level of necessity in construction are very necessary nowadays by the research findings were also high in the results. Next, the third objective was the strategies that can be implemented in the usage of 5G technology in the construction industry with the high results through research findings that has been made. The contribution is for the the students, industry, and for academic research in the future.